1994
DOI: 10.1063/1.357589
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric properties and fatigue of PbZr0.51Ti0.49O3 thin films of varying thickness: Blocking layer model

Abstract: Ferroelectric capacitors having Pt bottom and top electrodes and a ferroelectric film of composition PbZr0.51Ti0.49O3 (PZT) were fabricated and investigated. The PZT films of thicknesses varying from 0.12 to 0.69 μm were prepared by organometallic chemical-vapor deposition. Annealed capacitors were investigated by capacitance, hysteresis, and pulse switching measurements. It is found that the thickness dependence of the reciprocal capacitance, the coercive voltage, and the polarization measured by pulse switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
113
3
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(128 citation statements)
references
References 18 publications
4
113
3
2
Order By: Relevance
“…These detrimental layers induce a significant voltage drop. 2,3 As d decreases, E C increases: E C ∝ d -1 . [2][3][4][5][6] Due to the lattice mismatch between the film and substrate, strain may develop inside the FE film.…”
Section: -12mentioning
confidence: 99%
“…These detrimental layers induce a significant voltage drop. 2,3 As d decreases, E C increases: E C ∝ d -1 . [2][3][4][5][6] Due to the lattice mismatch between the film and substrate, strain may develop inside the FE film.…”
Section: -12mentioning
confidence: 99%
“…2,3 The passive layer model suggests that the cyclic switching of the sample results in growth of the low-dielectric constant interface layer. [4][5][6] As a result, the field applied to the bulk of ferroelectric decreases which leads to decrease of the residual polarization.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, it was revealed that the inverse of the measured capacitance varies linearly with the film thickness. 1,2,[9][10][11][12][13][14][15] This observation led to a widely accepted interpretation of the experimental data in terms of a "series capacitor model." 9 According to such model, the measured capacitance density c t can be described by the relation…”
Section: Introductionmentioning
confidence: 99%